2015
DOI: 10.11648/j.ajep.20150406.17
|View full text |Cite
|
Sign up to set email alerts
|

Land Use-Land Cover Change and Drivers of Deforestation in the Patako Protected Area (Center-West of Senegal)

Abstract: Abstract:This study focus on land use-land cover changes relation to the multidimensional characteristics of spatial and temporal patterns of land dynamics and social practices. The objectives are to characterize the dynamics of land-use and landcover changes from 1992 to 2015, and to identify the drivers of deforestation and land degradation. Nine (09) types of classes were identified: humid vegetation (HV), savanna/wooded savanna (WS), savanna/shrub savanna (SSS), shrub savanna (SS), mangrove (MA), grass sav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The notable activities include the cutting down of trees, charcoal burning and poor farming methods, among others, which undermine the functionality of ecosystems [2]. The rapid conversion of natural vegetation, for example, to farmlands, could be attributed to farming techniques and agronomic approaches that aim at modern agricultural intensification [3]. For instance, in the Equateur province of the Democratic Republic of Congo, the agricultural expansion through shifting cultivation is the main proximate cause of deforestation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The notable activities include the cutting down of trees, charcoal burning and poor farming methods, among others, which undermine the functionality of ecosystems [2]. The rapid conversion of natural vegetation, for example, to farmlands, could be attributed to farming techniques and agronomic approaches that aim at modern agricultural intensification [3]. For instance, in the Equateur province of the Democratic Republic of Congo, the agricultural expansion through shifting cultivation is the main proximate cause of deforestation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns of land use trend over the time were described in other West African countries. These include studies in southern Burkina Faso (Ouedraogo et al, 2010), western Senegal, (Sambou et al, 2015) and south-eastern Senegal (Faye et al, 2016). A study carried out by USGS (USGS, 2016b) in a 38-year period (1975 to 2013) showed that the fastest average annual rate of cropland expansion in West Africa were found in Togo, Benin, Chad, Mauritania and Burkina Faso and in every country of the same region, agriculture was exerting pressure on the natural landscapes, replacing fragmented savanna, woodland and forests.…”
Section: Land Use Land Cover Changes In the Overall Acm From 1987 To mentioning
confidence: 99%
“…The main land use activities that have major adverse effect to forest conservation in the Lakhari WLS are increasing habitation, growing agricultural and forest-based livelihood activities, forest fire and illicit timber felling. Studies have well established that these land use activities have profound impact on ecological system and biodiversity in both direct and indirect ways (Mockrin et al 2017;Mon et al 2012;Sambou et al 2015). It removes and fragments native habitat, diminishes water quality, fosters exotic species invasions, increases predation by mesopredators and pets, and introduces pollutants (McCarty and Kaza 2015;Radeloff et al 2009).…”
Section: Land Use Changementioning
confidence: 99%